Direct Stimulation of Adult Neural Stem/Progenitor Cells In Vitro and Neurogenesis In Vivo by Salvianolic Acid B - Zhuang, Pengwei; Zhang, Yanjun; Cui, Guangzhi; Bian, Yuhong; Zhang, Mixia; Zhang, Jinbao; Liu, Yang; Yang, Xinpeng; Isaiah, Adejobi Oluwaniyi; Lin, Yingxue; Jiang, Yongbo (PLOS ONE, 2012)
Background Small molecules have been shown to modulate the neurogenesis processes. In search for new therapeutic drugs, the herbs used in traditional medicines for neurogenesis are promising candidates. Methodology and Principal Findings We selected a total of 45 natural compounds from Traditional Chinese herbal medicines which are extensively used in China to treat stroke clinically, and tested their proliferation-inducing activities on neural stem/progenitor cells (NSPCs). The screening results showed that salvianolic acid B (Sal B) displayed marked effects on the induction of proliferation of NSPCs. We further demonstrated that Sal B promoted NSPCs proliferation in dose- and time-dependent manners. To explore the molecular mechanism, PI3K/Akt, MEK/ERK and Notch signaling pathways were investigated. Cell proliferation assay demonstrated that Ly294002 (PI3K/Akt inhibitor), but neither U0126 (ERK inhibitor) nor DAPT (Notch inhibitor) inhibited the Sal B-induced proliferation of cells. Western Blotting results showed that stimulation of NSPCs with Sal B enhanced the phosphorylation of Akt, and Ly294002 abolished this effect, confirming the role of Akt in Sal B mediated proliferation of NSPCs. Rats exposed to transient cerebral ischemia were treated for 4 weeks with Sal B from the 7th day after stroke. BrdU incorporation assay results showed that exposure Sal B could maintain the proliferation of NSPCs after cerebral ischemia. Morris water maze test showed that delayed post-ischemic treatment with Sal B improved cognitive impairment after stroke in rats. Significance Sal B could maintain the NSPCs self-renew and promote proliferation, which was mediated by PI3K/Akt signal pathway. And delayed post-ischemic treatment with Sal B improved cognitive impairment after stroke in rats. These findings suggested that Sal B may act as a potential drug in treatment of brain injury or neurodegenerative diseases.